Factors Influencing The Muslim Consumer’s Level Of Confidence On Halal Logo Issued By Jakim An Empirical Study - MASNONO, AHMADI (2005)
Realizing the great demand of halal food in Malaysia and in the world in general, there are efforts by the Government to make Malaysia as a regional hub for halal food products. However, there is a situation now when consumers start questioning about the actual halal content of products that have been certified as halal by JAKIM. This scenario happens due to the actions by certain manufacturers that do not fully comply to the JAKIM requirement in meeting the specified halal standard.